Fertile ground: enhancing local food production in Delft, South Africa - Pieters, Frans (School of Architecture, Planning and Geomatics, 2017)
This dissertation, situated in Delft, on the eastern edge of Cape Town, aims to improve livelihoods by establishing a productive urban agricultural operation that will create jobs, supply healthy food and reestablish farming as a lucrative business in an impoverished community. It is intended to inspire people to transform the landscape of local food production and sustainable agricultural practice. Most impoverished communities tend to feel the effects of a formal food system that is set up to deliver to more established urban areas. This forces low-income communities to rely on informal retail to supply healthy foods, often at a premium, both for user and supplier. Food supply chains are dispersed resulting in high food costs and over-reliance on an extensive transportation sector. My project aims to decrease this footprint allowing nutritious foods to be grown and sold locally, benefitting both the consumer and the producer. By investigating the leading NGOs promoting urban agriculture and food security in the Western Cape, I have been able to extract valuable spatial lessons from these organizations. I have then applied them to create a model of urban agriculture and local food production that can work in these demanding landscapes. I explored the natural and urban conditions at various scales to determine the number of inputs required for a successful operation. I also investigated selected technologies to enhance land productivity and food production as well as selected systems to establish a sustainable operation in a landscape where resources are valuable and scarce. With high unemployment a regular statistic in impoverished communities, there will always be labor available and when given the opportunity, local residents can take advantage of the many benefits that such a project can deliver. I hope to develop a model that can be implemented around communities all over South Africa and the world, where common challenges of food insecurity faced by millions of people everyday can be addressed through local food production and in the process, establish a new type of agricultural model that can supply both the formal and the informal food sectors. My project is about celebrating a new agricultural model, one that is integrated into the urban landscape with a particular focus on local production within an impoverished community. It consists of a production farm with educational, research and retail components and a large-scale greenhouse that is intended to change the landscape of Delft. The farm will run various agricultural operations in a sustainable manner where are resources and waste is recycled and reused allowing for a closed loop operation. Growing, processing, packaging and distributing of produce will take place from this centralized hub. The greenhouse will be the celebratory moment of my project and I envision it to transform the landscape of Delft and the way in which the farming is perceived from a local perspective. The building will showcase all kinds of food growing technologies and will become a landmark in the area as a place of education and production. Specialized crops and seeds will be cultivated, stored and displayed for visitors from around the world, a one of a kind building that fuses food production, education and public interaction.